2019
DOI: 10.1017/jns.2019.21
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of daily selenium intake by 3- to 5-year-old Japanese children based on selenium excretion in 24-h urine samples

Abstract: To evaluate the daily Se intake of 3- to 5-year-old Japanese children, we used seventy-two urine samples collected from fifty-three children (twenty-seven male and twenty-six female) from two cities in Miyagi prefecture, Japan. For measuring low Se concentrations with high precision, accuracy and rapidity in the 24-h urine samples, we developed an instrumental neutron activation analysis (INAA) method, that is without any chemical separation, using the short-lived 77mSe (t1/2 = 17·4 s) nuclide. The estimated S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Urinary Se excretion is one of the most effective indicators of Se intake (Rodríguez et al, 1995 ; Hawkes et al, 2003 ; Yoneyama et al, 2008 ) which suggest that USeC can be used to predict the Se intake of different populations (Longnecker et al, 1996 ; Nakamura et al, 2019 ). The median USeC for school-age children and women of reproductive age were comparable to or less than USeC values reported by Phiri et al ( 2020 ) for a Malawian population, who were reported to be Se deficient based on their plasma Se status.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Urinary Se excretion is one of the most effective indicators of Se intake (Rodríguez et al, 1995 ; Hawkes et al, 2003 ; Yoneyama et al, 2008 ) which suggest that USeC can be used to predict the Se intake of different populations (Longnecker et al, 1996 ; Nakamura et al, 2019 ). The median USeC for school-age children and women of reproductive age were comparable to or less than USeC values reported by Phiri et al ( 2020 ) for a Malawian population, who were reported to be Se deficient based on their plasma Se status.…”
Section: Discussionmentioning
confidence: 99%
“…The USeC reflects Se intake and approximately 40–60% of Se intake is excreted in urine (EFSA NDA Panel, 2014 ), which, for the current study, means that approximately 32–54% participants of the surveyed population is living at risk of Se deficiency (USeC uncor , USeC sg ) but 7–30% when USeC cre is used. A study investigating daily Se intake in a Japanese population from 24-h urinary Se reported 73 and 77% of ingested Se excreted via urine in men and women, respectively (Nakamura et al, 2019 ; Yoneyama et al, 2008 ). If urine samples collected in our study are assumed equivalent to 24-h urine sampling, then the mean Se intake based on USeC uncor and USeC sg in males and females of all age groups ≥ 14 years would be less than the EAR (45 µg/day).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation